NIETZSCHE’S NIHILISM AND MIMETIC STUDIES - García-Granero, Marina (Homo Mimeticus II, 2024)
It is uncontroversial to present Friedrich Nietzsche’s diagnosis of nihilism as one of his most important legacies for contemporary thought. Among his ideas, the thought of the death of God has significantly impacted European culture; it also provokes vivid discussions within mimetic theory and is now under the lens of mimetic studies as well. Although Nietzsche was not the first thinker to speak of nihilism, and there is an important "prehistory" of nihilism crucial to understanding where his originality and contribution lie, he is responsible for formulating nihilism as a vital question in philosophy. My goal is to provide an